Characterization of flowing liquid films as a regenerating plasma mirror for high repetition-rate laser contrast enhancement. (18th June 2020) - Underwood, C. I. D.; Gan, G.; He, Z.-H.; Murphy, C. D.; Thomas, A. G. R.; Krushelnick, K.; Nees, J.
Abstract: In this paper, we characterize a high repetition-rate regenerating plasma mirror produced by the thin film of liquid formed when two laminar streams collide. The use of a flowing liquid film is inexpensive and the interaction surface refreshes automatically, avoiding buildup of on-target debris. The composition of the liquid material and the relative angle of the film-generating nozzles was optimized for this application. Spectra measured in reflection from a water-based plasma mirror showed a blue shift but an optical reflectivity of up to 30%. The thickness of the film was found to be of the order of 2 μ m, and the stability of the reflected spot was ≈ 1 mrad. The reflected beam profile was highly distorted but stable. Further optimization of the nozzles to affect the fluid flow should enable significant improvements in control of the fluid films and increase in the reflectivity of these mirrors.